Pornoboscodidascalus Latinus (1624) : Kaspar Barth's Neo-Latin Translation of Celestina - Rojas, Fernando de, -1541 (Book collections on Project MUSE., 2017)
In 1624 the German erudite Kaspar Barth translated the Spanish bookCelestina(1499) into Neo-Latin with the titlePornoboscodidascalus("teacher of the brothel master"). The translation, intended for the cultivated readers who still used Latin as their lingua franca, contained an extensive prologue and numerous translation notes. This first critical edition of Barth's translation is a valuable tool not only forCelestinascholars, but also for Neo-Latin scholars and for those interested in the history of translation and in early modern Europe. With such a wide readership in mind, the edition contains the transcription of the Neo-Latin text, as well as the English translation of Barth's prologue and notes. It also includes a critical apparatus, notes with full references to the sources quoted by Barth, and an introduction to the most relevant aspects of Barth's translation.